Drivers of Consumers Online Purchasing Intention in China on Singles’ Day - Zhao, Xiaqing (2015)
Purpose – The purpose of the present study is to understand the drivers of Chinese consumers online purchase intention on Singles’ Day so as to aid e-retailers in working out marketing programs that can help increase sales on that day.